Effect of Infiltration Ce0.8Sm0.2O1.9 Against Double Perovskite Performance LaBa0.5Sr0.5Co2O5+δ as IT-SOFC Cathode - Adi Subardi; Yen-Pei Fu (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Modifying the sample surface by infiltration technique using Ce0.8Sm0.2O1.9 (SDC) electrolyte has been done to increase the catalytic activity of the LaBa0.5Sr0.5Co2O5+δ (LBSC) cathode. The cathode powder structure was evaluated using X-ray diffraction (XRD) at room temperature, and the LBSC cathode microstructure was analyzed using scanning electron microscopy (SEM). The electrical conductivity of the LBSC cathode was tested using the four-probe DC method. Symmetrical cells were tested using a potentiostat Voltalab PGZ 301 and a digital source meter Keithley 2420. LBSC powder was discovered to have a tetragonal structure (space group: P4/mmm) with lattice parameters of a = 3.86253 Å, c = 7.73438 Å, and V = 115.338 Å. From the SEM image, the LBSC cathode has homogeneous, dense, and highly porous grains. The electrical conductivity showed metallic behavior, gradually decreasing from 167 S.cm-1 at 300℃ to 105 S.cm-1 at 800℃. A significant increase in current density (io) of 275% occurred at 800℃ from 154.10 mA.cm−2 (pure LBSC) to 577.86 mA.cm−2 (LBSC+0.5M SDC). The activation energy value (Ea) of symmetrical cells was determined using electrochemical impedance spectroscopy (EIS), low-field (LF), and high-field (HF) techniques. The activation energy of the LBSC+0.5 M SDC specimen was 47.9 kJ mol-1 or 79.4% lower than the activation energy of the LBSC cathode specimen without infiltration at atmospheric pressure of 0.03 atm. These results indicate that SDC infiltration of the LBSC cathode can reduce the activation energy of the signiﬁcant. The cathode membrane adheres quite well to the electrolyte membrane, the cathode porosity varies in the range of 1–4 µm, and the grain size is 0.1–1.5 µm.